Workload, achievement motivation, and mental fatigue: a mediation study among white-collar workers - Shamala Ramasamy; Tan, Cheryl Mei Nee; Mohammed Irfan Abdul Malick Sahib (Penerbit Universiti Kebangsaan Malaysia, 2023)
Workplace fatigue has long been a plague in most countries as the expectation of employee performances is overstretching. Fatigue is attributed by job demand as workload depletes energy. However, job resources such as organizational, physical, or social characteristic as well as work motivation tend to buffer fatigue. The aim of this paper is to analyse the mediation effects of achievement motivation in the relationship between workload and mental fatigue among white-collared workers, by using Mc Clelland’s theory of motivation and Job DemandResources model. A cross-sectional survey design was employed. Total of 117 males and 201 females responded to a self-report questionnaire consisting of the Workload subscale from Job Demands-Resources Scale, the Achievement Motivation subscale from Manifest Needs Questionnaire, and the Mental Fatigue Scale. Mediation model was employed. Results revealed that workload significantly predicts mental fatigue, and that achievement motivation is a significant partial mediator in the relationship between mental fatigue and achievement motivation. Findings imply that organizations would benefit from investing in higher levels of achievement motivation aiding in reducing levels of mental fatigue. Avoid compelling employees in handling extremely high workload, as achievement motivation only buffers the impact of mental fatigue.